Limiar de detecção de larvas de Toxocara canis em leite bovino experimentalmente contaminado - Pereira, Edlayne Larissa Gretter Machado (2015)
This study aimed to evaluate the limit of detection of Toxocara canis larvae in experimentally contaminated commercial bovine milk, based on a centrifuge-sedimentation technique. Firstly, bovine milk (integral and skim) samples were contaminated with 50 T. canis larvae, in order to evaluate the interference of milk fat on the recovery of the larvae. The second step of the study was to verify the influence of formalin 10% (100 µL), ether (100 µL) and combination of both solutions. The third step consisted of studying the limit of detection of larvae, using the best solution (step 2) for degreasing the milk. Samples were contaminated with aliquots of 1; 5; 10; 25 and 50 larvae. For each milk sample (1.0 mL), 15 repetitions were analyzed. It was observed that the recovery of the larvae from the skim milk was higher (p= 0.0031) than those from the integral milk. There was no significant difference (p= 0.5681) regarding the percentage of recovered larvae in comparing the degreasing solutions. Nevertheless, the formalin-ether combination was more efficient to recover the larvae (73.1%) in comparison to the ether (71.9%), the pure integral milk (70.0%) as well as the formalin (67.6%). Concerned to the limit of detection (using formalin-ether), all the samples contaminated with 5; 10; 25 and 50 larvae were positive (minimum: 62.7%). The samples contaminated with a single larva, 66.7% were positive. The technique may be useful for recovering Toxocara spp. larvae in milk samples of a wide range of animal species, either naturally or experimentally contaminated.